Forest biodiversity in Andean brow and its relation to the carbon content in the above-ground biomass - Marco Vinicio Rodríguez Llerena; Diego Armando Damián Carrión; Guido Patricio Santillán Lima; Celso Guillermo Recalde Moreno; Franklin Enrique Cargua Catagña (Acta Agronómica, 2017)
The aim of this research was to determine the biodiversity indices and its relation to the carbon content (C) in the above-ground biomass, in the Andean brow forest located in the buffer zone of the Sangay National Park in Ecuador, where twelve permanent sampling plots were established. It was identified 19 species, 18 genuses, and 17 families with a total of 518 individuals from which Melastomataceae is one of the most representative families encompassing the Miconia genus with 159 individuals (30.70%), this information is relevant due this plant group can be utilized as an indicator of the conservation state of these forests in danger of disappearing. The highest concentration of C present in the above-ground biomass is recorded in the Guangra Bajo location (182.24 ton.ha-1), these values are related to the high biodiversity of Shannon species (0.90) and Simpson (0.87), the lowest values of C in the above-ground biomass are presented in the Yunguilla sector (30.56 ton.ha-1), as follows: Shannon (0.89) and Simpson (0.71). Based on the foregoing, the Andean brow forest must be considered as a carbon sink in order to mitigate the effects on climate change, and thus the greatest benefit with regard to the capture of C as an ecosystem service will be obtained. This have allowed the conservation of these resources and the continuous provision of goods and environmental services to the area.